Current sensor-free transfer window alignment with combined energy harvesting and current measurement capabilities - Tim McRae (Power Electronic Devices and Components)
An energy harvesting circuit has been developed to power an IoT network which measures energy consumption at the outlet level. This work integrates the rectification and down-stream voltage regulation stages, allowing the capacitor voltage to be used to measure current. An experimental prototype is developed to demonstrate the proposed algorithm.